Kontribusi Pendidik Dalam Revitalisasi Bahasa Daerah Pada Kurikulum Merdeka Belajar - Wiguna, I Komang Wahyu (Edukasi: Jurnal Pendidikan Dasar, 2023)
This study was conducted to gather sufficient information on the contribution of educators in revitalizing regional languages in the independent learning curriculum. The method used in this study is through a literature study that collects several previous studies and existing policies from the government to answer what is the contribution of educators in revitalizing regional languages in the independent learning curriculum. The results of this study indicate the need for an increase in human resources for educators, especially those who are obliged to equip themselves with their respective regional languages. Educators must reflect a love for the local language before it is transmitted to their students. Educators can also contribute to developing and utilizing cultural wealth to strengthen the nation's character and the welfare of the people by inviting their students to make several projects related to their local culture. In addition, updating learning facilities and infrastructure is needed to accommodate the publication of students' work. The highlight of this activity is a tiered festival at the group level, education unit, to district/city and provincial level.